Political Change in the Theories of Alain Badiou and Jacques Ranciѐre - Jonutis, Karolis (Sociologija. Mintis ir veiksmas, 2017)
This article discusses the conceptualizations of political transformation, proposed in the political theories of Alain Badiou and Jacques Rancière. These authors criticize the disappearance of ideological differences in modern liberal democratic states. As their subject, they choose the marginal parts of society, which can make a rupture in an existing status quo by acting collectively and rebelliously. Both authors propose theories of praxis, in which thoughts have an influence on the material world and, on the opposite, the material world having influence on theory. This article examines the transformational logic of these political concepts and tries to reveal their main limitations.